Regional Priorities of Green Economy - Bobylev, Sergey Nikolayevich; Kudryavtseva, Olga Vladimirovna; Yakovleva, Yekaterina Yuryevna (Economy of Regions, 2015)
The article is dedicated to transforming the economy of Russian regions to a green economy, which is an essential factor for the sustainable development. This is important not only for Russia but the whole world because our country has the great natural capital and provides important environmental services that support the planet biosphere. Based on the analysis of economic, social and ecological statistical data and Human Development Index (HDI) we have shown that the development of Russian Federal Districts is very unbalanced and each Russian region has its own way to new economic model. For instance, it is necessary to increase the well-being in the North Caucasus Federal District, it is important to reach higher life expectancy at birth in the Siberian and the Far Eastern Districts. It is necessary to move from the «brown» economy to a green one by using the human capital (building a knowledge economy), by applying Best Available Technologies (Techniques), by investing in efficiency of use of natural resources and by increasing energy efficiency. The transition to a green economy will help to achieve social equity and the development of human potential; it helps to move from the exploitation of non-renewable natural capital to renewable human capital. All these socio-economic measures should give decoupling effect, make risks lower, reduce the exploitation of natural capital, stop the environmental degradation and prevent the ecological crisis. Transition to the green economic model has to be accompanied by new economic development indicators, which take into account social and environmental factors.